2014
DOI: 10.1098/rsta.2013.0342
|View full text |Cite
|
Sign up to set email alerts
|

Instability of supersonic compression ramp flow

Abstract: The instability of supersonic compression ramp flow is investigated. It is assumed that the Reynolds number is large and that the governing equations are the unsteady triple-deck equations. The mean flow is first calculated by solving the steady equations for various scaled ramp angles α , and the numerical results suggest that there is no singularity for increasing ramp angles. The stability of the flow is investigated using two approaches, first by solving the linearized unsteady equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(49 citation statements)
references
References 11 publications
2
47
0
Order By: Relevance
“…(2002), based on Neiland’s (1970) reattachment theory, found that their computations were smooth past the second minimum without encountering singularity for up to 7.5. These findings were also confirmed by Logue, Gajjar & Ruban (2014).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…(2002), based on Neiland’s (1970) reattachment theory, found that their computations were smooth past the second minimum without encountering singularity for up to 7.5. These findings were also confirmed by Logue, Gajjar & Ruban (2014).…”
Section: Resultssupporting
confidence: 81%
“…(Blue symbols: compression corner) ▴, ○, ▪, ▾ & ▸: Smith & Khorrami (1991); ▫, ♦, & ♢: Logue et al. (2014); * & : Korolev et al. (2002).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies involving numerical simulations of the unsteady triple-deck equations have encountered difficulties and unexplained behaviour in the results. For example in the recent paper by Logue, Gajjar & Ruban (2014) on unsteady flow past a compression ramp the results showed the development of a wave packet that grew in amplitude and convected downstream. The techniques used in Logue et al.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques used in Logue et al (2014) to solve the unsteady triple-deck equations utilised high-order finite differencing in the streamwise direction, combined with Chebychev collocation in the wall-normal direction, and a variety of time-marching schemes were tested. In grid-refinement studies, the wave packet signal was not resolved spatially or temporally as seen in figure 6 of Logue et al (2014). No convincing explanation was available to explain this behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation